Are scrubs the new white coat? An exploration of MPharm students' experiences of wearing scrubs. (30th November 2022) - Richardson, C L; Davidson, D; Morrison, A
Abstract: Introduction: Many healthcare professionals and students wear uniforms while working in clinical environments which help develop professional identity, however, there is limited data regarding uniforms for pharmacy professionals in the UK. 1 Historically, pharmacists and some pharmacy students wore white coats which increased professionalism, yet they are not practical with clinical roles. 2 In September 2021, one UK School of Pharmacy introduced scrubs as a uniform for MPharm students for work-based learning (WBL) at several NHS hospital trusts. Aim: To explore the experiences of MPharm students wearing scrubs during WBL. Methods: MPharm students in years 2-4 (n=311) were invited to participate in a 5-item anonymous online questionnaire which consisted of open-ended and closed-ended questions to explore perceptions of wearing scrubs. Years 3 and 4 were asked additional questions to compare wearing scrubs with their prior WBL where they had to dress ''professionally''. The data underwent descriptive and content analysis. This project received institutional ethical approval (17759-2021). Results: 75 responses from years 2-4 were analysed (17%, 52%, and 31% respectively across the year groups, 24% overall response rate). Students were predominantly female (85%; n=64) and White British (52%; n=39). When asked how happy they were to wear scrubs on a Likert scale from '5-extremely happy' to '1- not at all', 92% (n=69) indicated they were extremely or moderately happy to wear scrubs (median=5; IQR 1). The accompanying free-text responses showed reoccurring groups of positive comments concerning: professionalism (21%), acceptance (24%), and identity (26%). Students viewed themselves as having a "shared identity, sense of professionalism and purpose and maturity" [P40]. More negative comments pertained to the sizing (13%), changing facilities (6%) and being mistaken for other professionals (9%). 44% (n=27) of year 3 and 4 students perceived a change in patients' attitudes since wearing scrubs with 20% (n=13) citing patients as appearing more comfortable: ''Patients take us much more seriously - they see us as healthcare professionals rather than just students. I think it gives us greater confidence in ourselves.''[P11]. Additionally, 39% (n=24) perceived a change in treatment from staff, with 10% of these students sharing that staff were more open to them being on the wards. ''we are taken more seriously by staff… there are no questions about why we are on the ward''[P22]. Discussion/Conclusion: The introduction of scrubs had a positive impact on student experience and contributed to a sense of belonging to the profession and within the ward environment. There were practical issues around sizing and changing facilities which should be considered at a local level but with mindfulness so as not to discriminate against individuals. Further data should be sought exploring the patient perspective and from students at other institutions. It should be noted that three NHS Trusts hosted placements and so there is some transferability. Scrubs are an appropriate and well-liked uniform for pharmacy students. Introducing scrubs across other Schools of Pharmacy could increase the professionalism, confidence, and socialisation of MPharm students whilst also creating a shared identity between pharmacy students, like that of the historic white coat. References: 1. Timmons S, East L. Uniforms, status and professional boundaries in hospital. Sociol Health Illn. 2011;33(7):1035-1049. 2. Briceland LL, Brewer JM, Dominelli A. The Impact of Pharmacy Student Participation in the White Coat Ceremony on Professionalization. Am J Pharm Educ. 2020;84(3):7689.